Green defense technology triple net zero energy, water and waste models and applications - Goodsite, Michael E.; Juhola, Sirkku (NATO science for peace and security series. Series C, Environmental security, 2017)
This book focuses on the ways in which military installations and small cities can implement and integrate triple net planning and energy, water, and waste sustainability strategies into broad installation operational management, arrive at the best decision, create policy and communicate effectively to stakeholders.